Morbidity pattern and its association with personal hygiene practices among school going children (11 to 15 years of age group) in Surendranagar, Gujarat, India - Thekdi, Komal P.; Kartha, Girija P.; Thekdi, Pukur I. (International Journal Of Community Medicine And Public Health, 2017)
Background: The Millennium development goals have firmly established the issues of ‘water, sanitation and hygiene on the global agenda. Public health importance of hand washing as well as its importance in reduction in some of the communicable diseases such as diarrhoea and acute respiratory infections (ARI) has been highlighted in many studies. Methods: A cross sectional study conducted in both private and government schools selected by simple random sampling. Each class had an enrolment of 50 students and all the students were interviewed through pre - tested questionnaire and clinical examination was done to find out health problems in a standardized way. Results: There were 366 boys and 134 girls in the study population. The awareness regarding personal hygiene practices was maximum for daily bath (84%); 49.8% of students had knowledge regarding health related problems and about 24.4% of children had health related problems. Conclusions: Majority of the health problems affecting school children are preventable by promotion of hygiene practices through proper health education by the teachers who are the first contacts.